2017
DOI: 10.1039/c6mb00824k
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibitors might prevent ischemic arrhythmias via microRNA-1 repression in primary neonatal mouse ventricular myocytes

Abstract: Ischemic arrhythmias are the main causes of sudden cardiac death. It has been reported that soluble epoxide hydrolase inhibitors (sEHis) could prevent arrhythmias; however, the underlying molecular mechanisms remain unclear. In recent years, the proarrhythmic role of microRNA-1 (miR-1) has been investigated. This study aimed to elucidate whether sEHis prevented ischemic arrhythmias by suppressing miR-1. The primary neonatal mouse ventricular myocyte model of miR-1 overexpression was established by incubating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Here, we demonstrated for the first time, that the sEHi t-AUCB dose-dependently suppressed miR-1 upregulation in ischemic myocardium, which might be one of the mechanisms underlying the anti-arrhythmic effect of sEHi. Consistently, our previous in vitro whole-cell patch-clamp recording demonstrated that the current density of I k1 was markedly decreased in miR-1 overexpression model of neonatal cardiac myocytes [ 24 ]. The decreased I k1 was an important proarrhythmic factor in cardiac myocytes..…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Here, we demonstrated for the first time, that the sEHi t-AUCB dose-dependently suppressed miR-1 upregulation in ischemic myocardium, which might be one of the mechanisms underlying the anti-arrhythmic effect of sEHi. Consistently, our previous in vitro whole-cell patch-clamp recording demonstrated that the current density of I k1 was markedly decreased in miR-1 overexpression model of neonatal cardiac myocytes [ 24 ]. The decreased I k1 was an important proarrhythmic factor in cardiac myocytes..…”
Section: Discussionsupporting
confidence: 80%
“…Most importantly, we found that t-AUCB suppressed miR-1 overexpression and restored the impaired target mRNA and protein, which further suggested that the inverse relationship between sEHIs and miR-1 expression. Moreover, we previous studies also showed the beneficial effects of sEHIs on the expression of miR-1 and its target arrhythmia-related genes in neonatal cardiac myocytes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble epoxide hydrolase inhibitor (sEHi) increases EET concentration by inhibiting their degradation (Duflot et al, 2014). EETs play an antiarrhythmic role by downregulating abnormally upregulated miR-1 and miR-133 in the myocardium after myocardial infarction (Gui et al, 2018;Liu et al, 2017), but the specific mechanism remains unclear ( Fig. 1).…”
Section: Arrhythmiamentioning
confidence: 99%
“…There is an emerging role of microRNA (miRNA) in connexins regulation of cardiomyocytes [15,16]. MiRNAs are short nucleotide sequences that bind to the 3′-untranslated region of mRNA, thereby regulating gene expression at the post-transcriptional level by inhibiting the translation of a protein or by promoting mRNA degradation.…”
Section: Introductionmentioning
confidence: 99%